Strength, weakness, opportunities, and threats analysis of India's nationwide lockdown: A desperate effort to tackle the potential impact of severe acute respiratory syndrome coronavirus 2 by the world's largest democracy - Seetharam Bhat Kulthe Ramesh; Bobby Joseph (Wolters Kluwer Medknow Publications, 2022)
Objective: To study the impact of nationwide lockdown during severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Materials and Methods: We performed a strength, weakness, opportunities, and threats analysis of this measure and its potential impact and the current preparedness of the society. Results: SARS-CoV-2 has led to extreme measures by many countries in the form of nationwide lockdown. India is the world's largest democracy with over 1.3 billion people was put under complete lockdown. This pandemic would test India's public health system, community participation, its capacity to innovative and its potential to overcome various challenges. With a lack of adequate testing, a lockdown is the only tool available. Conclusions: In the existing scenario, a complete lockdown is probably the best measure currently available; however, the post lockdown exit strategy is key to recover from this lockdown.